Trans-Religious Identity from the Edge? Promoting Interfaith Dialogue among Transgender Community in Yogyakarta - Achmad Fawaid (Graduate Program of Pontianak Institute of Islamic Studies, 2017)
Transgender issues, including those who have been called as ‘waria’, are diverse, complex, and evolving, particularly in Indonesia where the most inhabited people are Muslims commonly bringing with them any sexual and, sadly, religious stereotype to waria as marginal(ized) individuals. This paper aims to raise a question of our primordial understanding and religious experience on the existence of the transgender community. It focused on an empirical study of Kebaya (Keluarga Besar Komunitas Waria Yogyakarta), Yogyakarta’s Center for Transgendered, which is an NGO developed by transvestites in Yogyakarta to struggle against prejudice, acceptance, and HIV Aids. This study is not specifically to analyze their social relation, but importantly how the NGO became a shared space of interfaith dialogue and a representation of religios life among transgender people in Yogyakarta, including the ways they build socio-cultural-religious relation with other people and religious figures. It would be analyzed under socio-anthropological approach to religion by which this study reflect them as a part of the certain community who had special position in terms of interreligious dialogue. The implication of this study suggests that interfaith dialogue is possible, not only among the inner-circle of mainstream religious believers, but also among and from the edge community: from those who often feel ostracized within today’s trans-population in Indonesia.